Audit committee and audit fees in high regulated firms: moderating role of regulatory oversight / Norziaton Ismail Khan - Ismail Khan, Norziaton (Universiti Teknologi MARA, Cawangan Melaka, 2019)
This research is conducted under the Malaysian corporate setting that is unique due to its stringent regulatory oversight by the Bank Negara Malaysia on financial institutions. The Bursa Malaysia revamped its Listing Requirements to enhance the internal governance mechanisms, specifically on the roles and responsibilities of audit committees. Hence, it provides an opportunity to examine the association between audit committee characteristics namely independence, diligence and expertise, and audit fees from the demand side perspective for high regulated firms. The study uses multiple regression model to investigate the moderating effect of regulatory oversight and the association between audit committee and audit fees for a sample of 1045 firms-year observation during the period of 2013 to 2017. Four hypotheses are developed and tested. The results reveal that high regulated firms pay higher audit fees than less regulated firms due to its additional industry-specific regulator, which requires more audit effort thus increasing audit fees. The findings reveals shows that regulatory oversight strengthens the association between audit committee diligence and expertise, and higher audit fees for high regulated firms. However, audit committee independence is insignificant and thus rejected. Higher audit fees paid by high regulated firms act as a complementary role of the regulatory oversight function, not a substitute, for external audit monitoring. Hence, results supported the notion that regulatory oversight complements the external audit as monitoring mechanisms. This study is important to policy makers, practitioners and academic literature as it provides additional knowledge about the impact of audit committee characteristics, both high regulated firms and less regulated firms. It draws from two theories, namely, the agency theory and institutional theory, to form the framework and develop the hypotheses to be examined. The results reported in this research is based on limited sample for high regulated firms in Malaysia.